Effect of Coffee Consumption on Postoperative Ileus after Colorectal Surgery: A Meta-Analysis of Randomized Controlled Trials. (8th June 2022) - Zhu, Junjia; Xu, Wenlong; Sun, Qi; Geng, Jun; Yu, Yifeng; Zhao, Zhenguo
Abstract : Background. Postoperative ileus (POI) is an important complication after elective colorectal surgery, which prolongs hospital stay and increases hospital costs. Coffee has been reported to be beneficial for the recovery of gastrointestinal function. We aimed to investigate the effectiveness of coffee consumption in the treatment of POI, following elective colorectal surgery. Methods. A comprehensive literature search for medical subject heading (MeSH) terms, including coffee, caffeine, colon, rectum, and colorectal surgery was conducted in PubMed, Embase, and Cochrane Library until November 2021. A meta-analysis of postoperative outcomes was conducted to assess the effectiveness of coffee consumption on POI after colorectal surgery. Results. 726 articles were identified and six RCTs that captured 416 patients were included. The time to first defecation was reduced with postoperative coffee consumption compared to the control group (mean difference = − 15.03 h; 95% confidence interval: -17.79, -12.26; P < 0.00001 ). There was no difference in time to first flatus, time to tolerance for solid food, length of hospital stay, use of laxatives, reinsertion of nasogastric tube, need for reoperation, postoperative complications, and anastomotic leak between the groups. Coffee did not have any adverse effects. Conclusion. The current literature revealed that postoperative coffee consumption shortened the time to first defecation following elective colorectal surgery. Large sample and tightly controlled multicenter randomized clinical trials are needed to offer a more accurate evaluation of the efficacy of coffee.